CEO, innovation, and business performance – A bibliometric analysis and literature review - Parodi-Camano, Tobias; Vidal-Durango, Jhon-Víctor; Portnoy, Ivan (International Journal of Innovative Research and Scientific Studies, 2025)
The role of the CEO and its impact on innovation and business performance has gained increasing relevance in management and strategy research. This study examines how CEO characteristics influence business innovation and organizational outcomes, providing a theoretical framework that connects these elements. A systematic literature review and bibliometric analysis were conducted on 67 scholarly articles indexed in Scopus, applying the PRISMA methodology and using VOSviewer to identify key trends, influential authors, and thematic clusters. The findings identify five key CEO attributes that impact business innovation: transformational leadership, innovative behavior, narcissism, personality traits, and sociodemographic aspects. Transformational leadership fosters organizational creativity and strategic orientation toward innovation, while demographic factors such as gender, experience, and educational background influence how CEOs develop and implement innovation strategies. The study concludes that CEO leadership acts as a catalyst for innovation, but its impact depends on organizational and contextual factors that can amplify or limit its effect on business performance. There is no universal approach to fostering innovation; strategies must align with the CEO’s attributes and the competitive environment. This study contributes to the theoretical debate on CEO and innovation while offering practical insights for academics, professionals, and businesses, guiding future research and leadership strategies to enhance innovation and competitiveness.